La globalización de la alimentación reflejada en la construcción de la relación experto alimentario-lego - Navas López, Julia (Nómadas. Critical Journal of Social and Juridical Science, 2009)
This article analyses the process of constructing dimensions of the variable “expert’s perception of lay” in two periods: during the last food crisis of BSE in Spain (2000-2002) and from octuber 2007 to September 2008 (food tranquillity). The analysis is done from the anthropology of food with a qualitative methodology (semiestructure interview to 25 experts and 12 consumers). Three dimensions emerged: relationship expert-lay, the actor and his role and the morality of the expert. The use of this perspective provides a holistic approach to the phenomena studied.